Pengaruh Pelaksanaan Anggaran dan Kualitas Sumber Daya Manusia Terhadap Kinerja Manajerial Melalui Penyerapan Anggaran - Rahmatullah, Salsabila; Hermawan, Dharma; Nurhakim, Nurhakim; Fadli, Yusuf; Ramadhan, Sukma Aditya (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Currently, behind the glittering capital of Jakarta, there are still many problems of social inequality that occur. This social inequality is still felt by vulnerable groups, such as people with disabilities who live in the Jakarta Capital City settlements. The fulfillment of basic needs is a program established by the government aimed at the welfare of people with disabilities. This article specifically describes the program to fulfill the basic needs of people with disabilities. The research obtained was then analyzed and interpreted to see the extent to which the basic needs program had an impact on people with disabilities. Under the current era of government policies, basic needs programs are still being implemented in accordance with the provisions of the laws that have been implemented. In addition, the government provides the program in the form of the Jakarta Persons with Disabilities Card (JPDC). With the Jakarta Persons with Disabilities Card (JPDC), it is hoped that people with disabilities can easily obtain this assistance. The assistance is disbursed through a Bank DKI ATM independently. For recipients who do not have legal skills, they can provide a power of attorney to a trusted person, and for recipients who are underage, they can be represented by a parent or guardian by bringing a family card and birth certificate. The current basic needs program is still being implemented to this day to continue to prosper people with disabilities. For reference to better explain how the program to fulfill basic needs is carried out properly.